2020
DOI: 10.1021/acs.accounts.9b00527
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Electrochemical and Statistical Analysis Tools for Molecular Design and Mechanistic Understanding

Abstract: Conspectus Medicinal chemistry campaigns set the foundation for streamlined molecular design strategies through the development of quantitative structure–activity models. Our group’s enduring underlying interest in reaction mechanism propelled our adaption of a similar strategy to unite mechanistic interrogation and catalyst optimization by relating reaction outputs to molecular descriptors. Through collaborative opportunities, we have recently expanded these predictive statistical modeling tools to electrocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Recently, however, through the pioneering work of the Sigman and Sanford groups, these relationships have been shown to be effective for the development of multivariate linear regression (MLR) models to understand and predict the behavior of electrolyte materials for NAORFBs. These techniques and the general workflow for model development have been described in a recent Accounts of Chemical Research article by the Sigman group and is shown in Figure 7 [41] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, through the pioneering work of the Sigman and Sanford groups, these relationships have been shown to be effective for the development of multivariate linear regression (MLR) models to understand and predict the behavior of electrolyte materials for NAORFBs. These techniques and the general workflow for model development have been described in a recent Accounts of Chemical Research article by the Sigman group and is shown in Figure 7 [41] …”
Section: Discussionmentioning
confidence: 99%
“…These techniques and the general workflow for model development have been described in a recent Accounts of Chemical Research article by the Sigman group and is shown in Figure 7. [41] Briefly, predictive model generation for any property of interest generally follows the following workflow: (i) strategic data set isolation and characterization, (ii) quantum mechanical calculations to isolate desired parameters, (iii) statistical model development, and (iv) model extrapolation to generate highly desirable molecules which optimize the response value of interest. To describe this workflow, (i) an appropriate data set must first be isolated in order to "train" the computational model to be developed.…”
Section: Computational Tools For Rfb Electrolyte Understanding and Opmentioning
confidence: 99%
“…Electroanalytic methods, including voltammetry, spectroelectrochemistry, hydrodynamic electrodes, and scanning electrochemical microscopy, are powerful tools for investigating reaction mechanisms involving electron transfer events. 49 Recently, these analytical techniques that are widely used in energy research have seen increasing applications in organic synthetic systems. For example, voltammetry can reveal the redox properties of reactive species and provides kinetic information for reactive intermediates that are difficult to access using chemical techniques.…”
Section: Electrochemistrymentioning
confidence: 99%
“…[25][26][27] These robotized approaches are particularly auspicious as they enable obtaining reproducible data sets that, in concert with statistical analysis tools, allow for correlating reaction outputs to specific physico-chemical properties. [28][29][30] While recently, random forest models have gained attention for being excellent for prediction, 31 such models often tend to be difficult to interpret. 32 Hence alternative, multivariate linear and polynomial regression analyses enjoy great popularity in both industry and academia, 33 owing to their ease of interpretability.…”
Section: Introductionmentioning
confidence: 99%